Needs Analysis for the Development of a Contextual Physics Interactive E-Module Based on Deep Learning to Enhance Critical Thinking Skills - Etri Alga Vrimesty; Ratnawulan; Ahmad Fauzi; Emiliannur (Jurnal Penelitian Pendidikan IPA, 2026)
Physics learning at the senior high school (SMA/MA) level still faces challenges in developing students’ critical thinking skills. This is largely due to the use of instructional materials that are less interactive and the limited implementation of contextual learning approaches. On the other hand, the rapid advancement of digital technology provides significant opportunities to create more engaging, flexible, and meaningful learning experiences through digital-based media. This study aims to analyze the need for developing a contextual physics interactive e-module based on a deep learning approach to enhance students’ critical thinking skills. The research employs a Research and Development (R&D) method using the Plomp development model, which includes the preliminary research, prototyping phase, and assessment phase, with a focus on the need analysis stage. Data were collected through tests, questionnaires, interviews, and documentation studies related to the current learning conditions in schools. The results indicate that students prefer digital-based learning as it is more engaging, interactive, and accessible anytime and anywhere. Furthermore, schools have provided adequate supporting facilities such as technological devices and internet access. However, the use of digital teaching materials in physics learning is still not optimal and has not yet integrated contextual and deep learning approaches. Therefore, the development of an interactive e-module based on deep learning is highly needed as an innovative solution to improve students’ critical thinking skills.